Bar workers' health and environmental tobacco smoke exposure (BHETSE): symptomatic improvement in bar staff following smoke-free legislation in Scotland. Issue 5 (10th February 2009) - Ayres, J G; Semple, S; MacCalman, L; Dempsey, S; Hilton, S; Hurley, J F; Miller, B G; Naji, A; Petticrew, M
Abstract : Objective: To examine changes in the health of bar workers after smoke-free legislation was introduced. Design: Longitudinal study following bar workers from before legislation introduction, at 2 months after introduction and at 1 year to control for seasonal differences. Setting: Bars across a range of socio-economic settings in Scotland. Participants: 371 bar workers recruited from 72 bars. Intervention: Introduction of smoke-free legislation prohibiting smoking in enclosed public places, including bars. Main outcomes measures: Change in prevalence of self-reported respiratory and sensory symptoms. Results: Of the 191 (51%) workers seen at 1-year follow-up, the percentage reporting any respiratory symptom fell from 69% to 57% (p = 0.02) and for sensory symptoms from 75% to 64% (p = 0.02) following reductions in exposure, effects being greater at 2 months, probably partly due to seasonal effects. Excluding respondents who reported having a cold at either baseline or 1 year, the reduction in respiratory symptoms was similar although greater for "any" sensory symptom (69% falling to 54%, p = 0.011). For non-smokers (n = 57) the reductions in reported symptoms were significant for phlegm production (32% to 14%, p = 0.011) and red/irritated eyes (44% to 18%, p = 0.001). Wheeze (48% to 31%, p = 0.006) and breathlessness (42% to 29%, p = 0.038) improved significantly in smokers. There was no relationship between change in salivary cotinine levels and change in symptoms. Conclusions: Bar workers in Scotland reported significantly fewer respiratory and sensory symptoms 1 year after their working environment became smoke free. As these improvements, controlled for seasonal variations, were seen in both non-smokers and smokers, smoke-free working environments may have potentially important benefits even for smokers.